2010
DOI: 10.1111/j.1365-2966.2010.17380.x
|View full text |Cite
|
Sign up to set email alerts
|

A kinematical approach to gravitational lensing using new formulae for refractive index and acceleration

Abstract: This paper uses the Schwarzschild metric to derive an effective refractive index and acceleration vector that account for relativistic deflection of light rays in an otherwise classical kinematic framework. The new refractive index and the known path equation are integrated to give accurate results for travel time and deflection angle, respectively. A new formula for coordinate acceleration is derived which describes the path of a massless test particle in the vicinity of a spherically symmetric mass density d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…They showed that their linearized equations were capable of an exact closed-form solution which agreed well with the fully non-linear simulations. In the present paper, the approach of Walters et al (2010) is generalized to include the effects of relativistic frame dragging due to rotation of the lensing object, as described by the Kerr metric. A kinematic description is given in Section 2.…”
Section: Intensitymentioning
confidence: 99%
See 4 more Smart Citations
“…They showed that their linearized equations were capable of an exact closed-form solution which agreed well with the fully non-linear simulations. In the present paper, the approach of Walters et al (2010) is generalized to include the effects of relativistic frame dragging due to rotation of the lensing object, as described by the Kerr metric. A kinematic description is given in Section 2.…”
Section: Intensitymentioning
confidence: 99%
“…In order to check this result, we may compare it to the delay (∆t) calculated numerically to high precision using Gaussian quadrature with the formula given by Walters et al (2010). For a ray starting at earth orbit, grazing the sun (r0 = 696000km and rs = 2.95km) and reaching earth-orbit again, the travel time delay is calculated accurately for a range of orbital distances.…”
Section: Application: Travel Time Delay -Second Order Approximationmentioning
confidence: 99%
See 3 more Smart Citations